A study of ticks and tick-borne livestock pathogens in Pakistan - Karim, Shahid (PLoS Negl Trop Dis, 2017)
BACKGROUND: As obligate blood-feeding arthropods, ticks transmit pathogens to humans and domestic animals more often than other arthropod vectors. Livestock farming plays a vital role in the rural economy of Pakistan, and tick infestation causes serious problems with it. However, research on tick species diversity and tick-borne pathogens has rarely been conducted in Pakistan. In this study, a systematic investigation of the tick species infesting livestock in different ecological regions of Pakistan was conducted to determine the microbiome and pathobiome diversity in the indigenous ticks. METHODOLOGY/PRINCIPAL FINDINGS: A total of 3,866 tick specimens were morphologically identified as 19 different tick species representing three important hard ticks, Rhipicephalus, Haemaphysalis and Hyalomma, and two soft ticks, Ornithodorus and Argas. The bacterial diversity across these tick species was assessed by bacterial 16S rRNA gene sequencing using a 454-sequencing platform on 10 of the different tick species infesting livestock. The notable genera detected include Ralstonia, Clostridium, Staphylococcus, Rickettsia, Lactococcus, Lactobacillus, Corynebacterium, Enterobacter, and Enterococcus. A survey of Spotted fever group rickettsia from 514 samples from the 13 different tick species generated rickettsial-specific amplicons in 10% (54) of total ticks tested. Only three tick species Rhipicephalus microplus, Hyalomma anatolicum, and H. dromedarii had evidence of infection with “Candidatus Rickettsia amblyommii” a result further verified using a rompB gene-specific quantitative PCR (qPCR) assay. The Hyalomma ticks also tested positive for the piroplasm, Theileria annulata, using a qPCR assay. CONCLUSIONS/SIGNIFICANCE: This study provides information about tick diversity in Pakistan, and pathogenic bacteria in different tick species. Our results showed evidence for Candidatus R. amblyommii infection in Rhipicephalus microplus, H. anatolicum, and H. dromedarii ticks, which also carried T. annulata.